Precise and low-complexity method for underwater Doppler estimation based on acoustic frequency comb waveforms - Li, Jie; Qian, ZhiWen; Hong, DeYue; Zhai, JingSheng (Frontiers in Marine Science, 2024)
Ocean observation has advanced rapidly in recent decades due to its crucial role in resource exploration and scientific research, with the Doppler factor being widely utilized. However, the precision of Doppler estimation is frequently constrained by frequency resolution. Traditional frequency estimation methods using single-tone signals face considerable challenges with low accuracy and poor robustness. In response, this paper introduces a novel Doppler-sensitive Acoustic Frequency Comb (AFC) for estimating the Doppler factor, enabling multiple measurements with a single transmission and reception of the signal. The proposed Combined Uneven Uncertainty (CUU) method based on AFC achieves a bias of less than 1.1×10-5, significantly surpassing the optimal result of 3.2×10-5 attained by other frequency estimation methods in the absence of noise. Compared to traditional single-tone methods, the AFC approach improves spectral leakage performance and enhances estimation accuracy without increasing computational complexity. Experimental results demonstrate that the CUU method realizes a difference performance of less than 3.4×10-6, notably lower than that of 3.2×10-5 induced by coherent spectral leakage in fast Fourier Transform (FFT).